Analysis of Determinants of Corn Farmers' Income in Stabat District, Langkat Regency - Ulzannah, Nisa; Faried, Annisa Ilmi; Ramadhan, Anggia (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the determinants of corn farmers' income in Stabat District, Langkat Regency, using a mixed method approach. Data were collected from August 2025 to February 2026 through questionnaires, interviews, and observations of 195 respondents determined using the Slovin formula. The analysis was conducted using Confirmatory Factor Analysis (CFA) and multiple linear regression. The CFA results reduced eight variables into three main factors (Physical Resources, Human Resource Quality, and Market Mechanisms) that explained 68.7% of the variation in income. The regression test showed that Selling Price (beta=0.668), Land Area (beta=0.403), and Informal Education (beta=0.329$) had a positive and significant effect on income. Selling price was found to be the most dominant and sensitive factor to farmer welfare. The novelty of this study proves that informal education (extension) has a more strategic role than formal education in increasing income efficiency in the study location. Integratively, the income of corn farmers in Stabat is a unified system influenced by technical aspects of land, individual managerial capacity, and the stability of external market conditions )